Revisitando Enrique Pichon-Rivière: grupo interno, história de origem e contexto social - Okamoto, Marta Maria (2017)
This study aims at revisiting the theory of Operative Groups and its author, Enrique Pichon-Rivière, the importance of working with groups in different settings, its power and the vigor of such resource. From his theory, we circumscribe the concept of internal group for the interesting definition linked to what each person carries with him/her from his/her life history, which is updated when entering a group. Having this conceptual framework in mind, we go through his writings, starting from the origins of the term group and going as far as the strong influence his theory had on the reality of the Brazilian mental health in the 1970s and 1980s. Going one step further past, we return to the first years of his life and we follow his living in the northern region of Argentina, predominantly inhabited by Guarani Indians. We enter the delicate and painful moments of his life, the first years in Buenos Aires, psychiatry, psychoanalysis, Marxism, his concern with the collective. We experience his form of creation, which is based on the need of coexisting articulation of theory and practice in a dialectical way. The choice for such a path is not random as Pichon- Rivière aligned his life with his theory, linking the striking facts he lived with the creation of his concepts, making his theory as the outcome of the story of a life. This reflection put together with the revision of the elements the Pichonian perspective identifies in the groups, can instrumentalize and enhance the practices and, at the same time, when brought to the present day, can reinforce the power and the place of the groups